PENGARUH IKLIM ORGANISASI DAN KOMITMEN ORGANISASI TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) PEGAWAI DI LINGKUNGAN DINAS PENDIDIKAN KOTA TANGERANG PROVINSI BANTEN - Shintawati Shintawati (Jurnal Manajemen Pendidikan, 2014)
The objective of this research is to study information about the effect of organizational climate and organizational commitment on employe’s citizenship behavior (OCB) .This research by using survey method with path analysis applied in testing hypothesis. The sample size in this research was done to 65 employe’s with samples taken using simple random sampling. The data were analyzed by using descriptive analyses, regressive analysis, and line analysis method. The result shows that there are direct influence of the followings: (1) there is a positively direct effect of organizational climate on employe’s organizational citizenship behavior (OCB). .(2) there is a positively direct effect of organizational commitment on employe’s organizational citizenship behavior (OCB). (3) there is a positively direct effect of organizational climate on organizational commitment .It is expected that the results of the research could be implied in increasing and optimalizing employe’s organizational citizenship behavior (OCB), organizational climate and organizational commitment should be taken into account.